Composite material of CoNi layered double hydroxide and metal organic framework compound as well as preparation method and application of composite material
By using the composite material of CoNi layered double hydroxide and metal organic frame compound as co-reaction promoters, the problems of low sensitivity and poor stability of the existing chemiluminescence detection system are solved, and efficient chemiluminescence detection is achieved, with high sensitivity, stability and anti-interference ability.
Patent Information
- Application Number
- CN202411654832.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
The existing chemiluminescence detection system lacks catalysts with high stability and high sensitivity due to the slow decomposition rate of hydrogen peroxide and few reactive oxygen radicals.
A composite material of CoNi layered double hydroxide and metal organic frame compound was used as a co-reaction accelerator, and prepared under ultrasonic conditions through etching reactions to form a structure in which the CoNi layered double hydroxide outer layer was wrapped with Co-organic frame compound nanocubes.
It significantly enhances the characteristics of luminol chemiluminescence, improves the chemiluminescence intensity, enhances the sensitivity and stability of detection, and has anti-interference ability, which can provide accurate detection results.
Smart Images

Figure CN119500278A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of analysis and detection, and in particular to a composite material of CoNi layered double hydroxide and a metal organic framework compound, and a preparation method and application thereof. Background Art
[0002] Chemiluminescence is a light radiation phenomenon produced by the chemical reaction of two or more substances. After the luminescent molecules absorb the energy of the chemical reaction, the electrons jump from the ground state to the excited state, and release in the form of light radiation when returning to the ground state. Chemiluminescence has become a very promising analytical detection method due to its high sensitivity, wide linear dynamic range, and simple analytical method.
[0003] At present, traditional chemiluminescence usually uses luminol as the luminescent molecule and H2O2 as the co-reactant to produce an excited intermediate in an alkaline environment. When the intermediate returns to the ground state, it releases energy and emits it in the form of light, thereby producing visible light. However, this traditional co-reaction chemiluminescence (CL) system has the disadvantages of slow decomposition rate of hydrogen peroxide and few reactive oxygen free radicals produced, resulting in low sensitivity of chemiluminescence detection and poor stability of results. The prior art usually uses optimized experimental conditions (such as temperature, solution pH, etc.) and the addition of sensitizers or catalysts to solve the problems of low stability and sensitivity. However, there is still a lack of satisfactory catalysts with high stability and sensitivity to provide accurate detection results. Summary of the invention
[0004] In order to overcome the above technical problems, the present invention provides a composite material of CoNi layered double hydroxide and metal organic framework compound and its preparation method and application. The composite material has excellent stability and high sensitivity, and can provide accurate results for detection and analysis.
[0005] The invention provides a composite material of CoNi layered double hydroxide and metal organic framework compound, comprising: a CoNi layered double hydroxide outer layer and a Co-organic framework compound (Co-MOF) nanocube wrapped inside the outer layer.
[0006] Optionally, the average particle size of the composite material is 150-200 nm, the average thickness of the double hydroxide sheet structure in the outer layer of the CoNi layered double hydroxide is 1-5 nm, and the average particle size of the Co-MOF nanocubes is 95-148 nm.
[0007] Optionally, the content of Co in the composite material is 3.0%-5.5%, and the content of Ni is 0.02%-0.20%.
[0008] On the other hand, the present invention also provides a method for preparing the composite material described in the above technical solution, comprising the following steps:
[0009] The Co-MOF nanocube raw material, Ni source and solvent are mixed and then subjected to etching reaction to obtain the composite material.
[0010] Optionally, the Ni source is Ni(NO3)2·6H2O, and the mass ratio of the Co-MOF nanocube raw material to the Ni source is 10-1.5:1.
[0011] Optionally, the average particle size of the Co-MOF nanocube raw material is 100-150 nm.
[0012] Optionally, the solvent is ethanol, and the ratio of the Co-MOF nanocube raw material to the solvent is 1 mg: 0.7-1.2 mL.
[0013] Optionally, the etching reaction is carried out under ultrasonic conditions, the frequency of the ultrasound is 35-45 Hz, and the time is 50-70 min.
[0014] On the other hand, the present invention further provides the use of the composite material described in the aforementioned technical solution or the composite material obtained by the preparation method described in the aforementioned technical solution in chemiluminescence detection.
[0015] Optionally, the chemiluminescent detection is uric acid detection.
[0016] The present invention provides a composite material of CoNi layered double hydroxide and metal organic framework compound, and its preparation method and application. The composite material provided by the present invention comprises: a CoNi layered double hydroxide outer layer and a Co-organic framework compound (Co-MOF) nanocube wrapped inside it. In the study of CoNi layered double hydroxide, the inventor unexpectedly found that the composite material of the above structure shows high activity when catalyzing luminol-hydrogen peroxide to form chemiluminescence, and can significantly enhance the chemiluminescence characteristics of luminol. The composite material prepared by the present invention is added to a buffer solution containing hydrogen peroxide and luminol, showing a high chemiluminescence intensity, and its luminescence intensity is 587.7-883.0 times, 2.3-3.5 times and 1.4-2.2 times that of the blank, the added Co-MOF and the CoNi layered double hydroxide, respectively, indicating that it has excellent chemiluminescence co-reaction accelerator characteristics and can be used in chemiluminescence detection. In addition, the composite material provided by the present invention is used in uric acid detection, and the detection concentration range is 10 -4 -10 -8M, has high sensitivity, and the test results have high reproducibility. The test is repeated 5 times, and there is no big difference in the test results, indicating that the test results have high stability. In addition, the composite material of CoNi layered double hydroxide and metal organic framework compound provided by the present invention has high anti-interference ability and can provide accurate test results. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and other objects, features and advantages of the present invention will be apparent from the following description of preferred embodiments and accompanying drawings which illustrate the subject matter of the present invention and its use, in which:
[0018] Figure 1 3 are scanning electron microscope (SEM) images of Co-MOF and the composite materials prepared in Examples 1-4 and Comparative Example 1, wherein a is a SEM image of Co-MOF, b is a SEM image of the composite material prepared in Example 1, c is a SEM image of the composite material prepared in Example 2, d is a SEM image of the composite material prepared in Example 3, e is a SEM image of the composite material prepared in Example 4, and f is a SEM image of the composite material prepared in Comparative Example 1.
[0019] Figure 2 This is a graph of the chemiluminescence intensity of Co-MOF and the composite materials prepared in Examples 1-4 and Comparative Example 1.
[0020] Figure 3 is the chemiluminescence intensity after adding different concentrations of uric acid samples.
[0021] Figure 4 This is the linear relationship between uric acid and chemiluminescence intensity.
[0022] Figure 5 This is a comparison chart of the chemiluminescence intensity of uric acid detected 5 times repeatedly.
[0023] Figure 6 This is a graph showing the anti-interference test results when the composite material obtained in Example 3 is used for chemiluminescence detection. DETAILED DESCRIPTION
[0024] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0025] On one hand, the present invention provides a composite material of CoNi layered double hydroxide and metal organic framework compound, comprising: a CoNi layered double hydroxide outer layer and a Co-organic framework compound (Co-MOF) nanocube wrapped inside the outer layer.
[0026] In the study of CoNi layered double hydroxide, the inventor unexpectedly found that the composite material with the above structure showed higher activity than pure CO-MOF and pure CoNi layered double hydroxide in catalyzing luminol-hydrogen peroxide to form chemiluminescence, and could efficiently promote hydrogen peroxide to produce active oxygen, significantly enhancing the chemiluminescence characteristics of luminol. In addition, when used as a co-reaction promoter, the composite material with special morphology also showed excellent stability, reproducibility and anti-interference.
[0027] In some embodiments of the present invention, the average particle size of the composite material is 150-200 nm, specifically 150 nm, 160 nm, 170 nm, 176 nm, 181 nm, 184 nm, 190 nm or 200 nm; the average thickness of the double hydroxide sheet structure in the outer layer of the CoNi layered double hydroxide is 1-5 nm, specifically 1.2 nm, 2.1 nm, 3.5 nm, 4 nm, 4.7 nm, 5 nm or any thickness between the above thicknesses; the average particle size of the Co-MOF nanocubes is 95-148 nm, specifically 95 nm, 100 nm, 110 nm, 119 nm, 120 nm, 122 nm, 124 nm, 130 nm, 135 nm, 140 nm or 148 nm.
[0028] In some embodiments of the present invention, the Co content in the composite material is 3.0%-5.5%, specifically 3.0%, 3.4%, 4.1%, 4.6%, 5.1% or 5.5%; the Ni content in the composite material is 0.02-0.20%, specifically 0.02%, 0.06%, 0.10%, 0.14%, 019% or 0.20%.
[0029] Another aspect of the present invention further provides a method for preparing the composite material described in the above technical solution, comprising the following steps:
[0030] The Co-MOF nanocube raw material, Ni source and solvent are mixed and then subjected to etching reaction to obtain the composite material.
[0031] In the present invention, the nickel source etches the Co-MOF nanocubes, while the Ni 2+ and OH -A precipitation reaction occurs to form a CoNi double hydroxide sheet structure, which wraps around the Co-MOF nanocubes to form a composite material of CoNi layered double hydroxide and metal-organic framework compound.
[0032] In some embodiments of the present invention, the Ni source is Ni(NO3)2·6H2O, and the mass ratio of the Co-MOF nanocube raw material to the Ni source is 10-1.5:1, specifically 10:1, 6:1, 4:1, 2:1 or 1.5:1. In the present invention, the above ratio range can ensure that the obtained composite material has the aforementioned specific structure, and when used as a co-reaction promoter in a chemiluminescent system, the obtained chemiluminescent system has a strong luminescence intensity.
[0033] In some embodiments of the present invention, the average particle size of the Co-MOF nanocube raw material is 100-150 nm, specifically 100 nm, 110 nm, 120 nm, 125 nm, 130 nm, 140 nm and 150 nm and any particle size between the above values. The present invention does not specifically limit the source of the Co-MOF nanocube raw material. In an embodiment of the present invention, the Co-MOF nanocube raw material is prepared by the following method:
[0034] (1) Co(NO3)2·6H2O, cetyltrimethylammonium bromide (CTAB) and water are mixed to obtain a mixed solution;
[0035] (2) mixing dimethylimidazole and water to obtain a dimethylimidazole aqueous solution;
[0036] (3) After mixing the mixed solution and the dimethylimidazole solution, stirring and reacting, a Co-MOF nanocube raw material is obtained.
[0037] In an embodiment of the present invention, in step (1), the amount of CTAB is 1.5-2.0wt.% of Co(NO3)2·6H2O, specifically 1.5wt.%, 1.6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.% or 2.0wt.%; the concentration of Co(NO3)2·6H2O in the mixed solution is 0.020-0.040g / mL, specifically 0.020g / mL, 0.025g / mL, 0.027g / mL, 0.029g / mL, 0.030g / mL, 0.032g / mL, or 0.035g / mL; the mixing is carried out under stirring conditions, and the mixing time is 3-6min, specifically 3min, 4min, 5min or 6min.
[0038] In an embodiment of the present invention, in step (2), the concentration of the dimethylimidazole aqueous solution is 0.050-0.070 g / mL, specifically 0.050 g / mL, 0.053 g / mL, 0.056 g / mL, 0.058 g / mL, 0.060 g / mL, 0.065 g / mL, 0.068 g / mL or 0.070 g / mL; the mixing is carried out under stirring conditions, and the mixing time is 4-8 min, specifically 4 min, 5 min, 6 min, 7 min or 8 min.
[0039] In the embodiment of the present invention, in step (3), the stirring reaction time is 25-35min, specifically 25min, 30min or 35min; after the stirring reaction is completed, the reaction liquid obtained by the stirring reaction is preferably subjected to solid-liquid separation, and the obtained solid is washed and dried to obtain Co-MOF; the solid-liquid separation method is preferably centrifugal separation, and the speed of the centrifugal separation is preferably 5000-8000r / min, specifically 5000r / min, 5500r / min, 6000r / min, 7000r / min, 7500r / min or 8000r / min, and the centrifugal speed is preferably 1000r / min, 1500r / min, 2000r / min, 3000r / min, 4000r / min or 5000r / min. The speed time is preferably 5-15min, specifically 5min, 8min, 10min, 12min or 15min; the washing solution used for the washing is preferably ethanol, and the number of washings is preferably 3-5 times, specifically 3 times, 4 times or 5 times; the present invention has no special limitation on the temperature and time of the drying, as long as the dry Co-MOF can be obtained. In an embodiment of the present invention, the drying temperature is preferably 50-70°C, specifically 50°C, 55°C, 60°C, 65°C or 70°C, and the drying time is preferably 4-12h, specifically 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.
[0040] In the embodiment of the present invention, the water used in the preparation process of the Co-MOF nanocube raw material is preferably deionized water.
[0041] In some embodiments of the present invention, the solvent used in the preparation method of the composite material is ethanol; the dosage ratio of the Co-MOF nanocube raw material to the solvent is 1 mg:0.7-1.2 mL, specifically 1 mg:0.7 mL, 1 mg:0.8 mL, 1 mg:0.9 mL, 1 mg:1.0 mL, 1 mg:1.1 mL or 1 mg:1.2 mL.
[0042] In some embodiments of the present invention, the etching reaction is carried out under ultrasonic conditions; the frequency of the ultrasound is preferably 35-45 Hz, specifically 35 Hz, 37 Hz, 39 Hz, 40 Hz, 42 Hz or 45 Hz; the ultrasound time is 50-70 min, specifically 50 min, 53 min, 56 min, 58 min, 60 min, 63 min, 68 min or 70 min. In the present invention, ultrasonic vibration can promote the chemical reaction, accelerate the ion transfer rate, and shorten the reaction time.
[0043] In some embodiments of the present invention, after the etching reaction is completed, the reaction solution obtained by the etching reaction is further subjected to solid-liquid separation, and the obtained solid is washed and then dried. In some embodiments of the present invention, the conditions of the solid-liquid separation, washing and drying are the same as those in the preparation of the Co-MOF nanocube raw material, and are not repeated here.
[0044] Another aspect of the present invention provides the use of the composite material described in the above technical solution or the composite material obtained by the preparation method described in the above technical solution in chemiluminescence detection.
[0045] In some embodiments of the present invention, the chemiluminescent detection is uric acid detection.
[0046] In some embodiments of the present invention, the chemiluminescent detection uses luminol as the chemiluminescent molecule, H2O2 as the co-reactant, and the composite material as the co-reaction accelerator.
[0047] In some embodiments of the present invention, the chemiluminescent detection comprises the following steps:
[0048] (1) dispersing the chemiluminescent molecules in a buffer solution to obtain a dispersion of the chemiluminescent molecules;
[0049] (2) adding a coreactant, a coreaction accelerator and a sample to be tested to the dispersion of the chemiluminescent molecule to obtain a chemiluminescent system;
[0050] (3) Detecting the luminescence intensity of the chemiluminescence system.
[0051] In some embodiments of the present invention, standard solutions of the substance to be detected of different concentrations can be prepared and used as samples to be detected. The luminescence intensity of the standard solutions can be detected using the aforementioned steps (1)-(3) to draw a standard curve. Then, the luminescence intensity of the sample to be detected of unknown concentration can be detected using the aforementioned steps (1)-(3). The concentration of the sample to be detected can be determined based on the standard curve.
[0052] In some embodiments of the present invention, the buffer solution is a Na2CO3-NaHCO3 buffer solution with a pH of 9; the concentration of the chemiluminescent molecular dispersion is 17-20 μg / mL, specifically 17.0 μg / mL, 17.5 μg / mL, 18.0 μg / mL, 18.5 μg / mL, 19.0 μg / mL, 19.2 μg / mL, 19.5 μg / mL or 20 μg / mL; the co-reactant is hydrogen peroxide, and the concentration of the hydrogen peroxide is 9-11 mM, specifically 9mM, 10mM or 11mM; the co-reaction promoter is a buffer solution dispersion of the composite material, wherein the concentration of the buffer solution dispersion of the composite material is 8-12mg / mL, specifically 8mg / mL, 9mg / mL, 10mg / mL, 11mg / mL or 12mg / mL; the volume ratio of the dispersion of the chemiluminescent molecule to the hydrogen peroxide and the dispersion of the buffer solution of the co-reaction promoter is 100:0.9-1.1:0.9-1.1, preferably 100:1:1.
[0053] When the composite material of CoNi layered double hydroxide and metal organic framework compound provided by the present invention is used as a coreaction promoter to participate in chemiluminescence reaction, it has high chemiluminescence intensity, wide detection concentration range, good stability, high reproducibility and strong anti-interference ability.
[0054] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] (1) Preparation of Co-MOF
[0057] 0.1164g Co(NO3)2·6H2O and 0.002g CTAB were placed in 4mL deionized water and mixed for 4min under stirring conditions to obtain a mixed solution; 1.816g dimethylimidazole was placed in 28mL deionized water and mixed for 6min under stirring conditions to obtain a dimethylimidazole aqueous solution. After the mixed solution and the dimethylimidazole solution were mixed, the reaction was stirred for 30min. The obtained reaction mixture was centrifuged at a speed of 7500r / min for 10min, the supernatant was poured off, the obtained precipitate was washed with ethanol 3 times, and then dried at 60℃ for 5h to obtain a purple Co-MOF.
[0058] (2) Preparation of a composite material of CoNi layered double hydroxide and metal organic framework compound (the mass ratio of Co-MOF to Ni(NO3)2·6H2O is 10:1)
[0059] 28 mg of Co-MOF, 2.8 mg of Ni(NO3)2·6H2O and 25 mL of ethanol were mixed and ultrasonicated at a frequency of 40 Hz for 60 min. The ultrasonic reaction solution was centrifuged at 5000 r / min for 5 min, the supernatant was discarded, and the precipitate was washed with ethanol three times. The washed precipitate was dried at 60 ° C for 12 h to obtain a composite material of CoNi layered double hydroxide and metal organic framework compound.
[0060] Example 2
[0061] A composite material was prepared according to the method of Example 1, except that the mass of Ni(NO3)2·6H2O was replaced by 4.7 mg (ie, the mass ratio of Co-MOF to Ni(NO3)2·6H2O was 6:1).
[0062] Example 3
[0063] A composite material was prepared according to the method of Example 1, except that the mass of Ni(NO3)2·6H2O was replaced by 7 mg (ie, the mass ratio of Co-MOF to Ni(NO3)2·6H2O was 4:1).
[0064] Example 4
[0065] A composite material was prepared according to the method of Example 1, except that the mass of Ni(NO3)2·6H2O was replaced by 14 mg (ie, the mass ratio of Co-MOF to Ni(NO3)2·6H2O was 2:1).
[0066] Comparative Example 1
[0067] A composite material was prepared according to the method of Example 1, except that the mass of Ni(NO3)2·6H2O was replaced by 28 mg (ie, the mass ratio of Co-MOF to Ni(NO3)2·6H2O was 1:1).
[0068] The Co-MOF prepared according to step (1) of Example 1 and the composite materials prepared in Examples 1-4 and Comparative Example 1 were tested by scanning electron microscopy (SEM). The results are as follows: Figure 1 shown. Figure 1In the figure, a is a SEM image of Co-MOF, from which it can be seen that Co-MOF is a uniform nanocube structure, and the average particle size (i.e., the average value of the longest diameter of the particles) is 125 nm; bf are SEM images of the composite materials obtained in Examples 1-4 and Comparative Example 1, respectively. From b, it can be seen that the particle size of the composite material obtained in Example 1 is 170 nm, and a thin layer of CoNi layered double hydroxide nanomaterial is formed on the surface of the Co-MOF nanocube. The average thickness of the sheet structure in the CoNi layered double hydroxide is measured to be 1.2 nm, and the average particle size of the Co-MOF nanocube is 124 nm. , the Co content was 5.1% and the Ni content was 0.02% as measured by X-ray energy dispersive spectrometer (EDS). Due to the small amount of Ni(NO3)2·6H2O used, the formed CoNi layered double hydroxide nanomaterial could not be evenly wrapped around the Co-MOF nanocubes; from c, it can be seen that the composite material obtained in Example 2 is a structure in which the CoNi layered double hydroxide is evenly wrapped around the Co-MOF nanocubes, and its average particle size is 176nm, wherein the thickness of the CoNi layered double hydroxide layer is 2.1nm, and the particle size of the Co-MOF nanocubes is 122nm, The content of Co is 4.6%, and the content of Ni is 0.06%. From d, it can be seen that the composite material obtained in Example 3 is a structure in which CoNi layered double hydroxide is uniformly wrapped around Co-MOF nanocubes, and its average particle size is 181nm, wherein the thickness of the CoNi layered double hydroxide layer is 3.5nm, the particle size of the Co-MOF nanocube is 120nm, the content of Co is 4.1%, and the content of Ni is 0.1%. From e, it can be seen that the composite material obtained in Example 4 is a structure in which CoNi layered double hydroxide is uniformly wrapped around Co-MOF nanocubes, and its average particle size is 181nm. The particle size is 184nm, of which the thickness of the CoNi layered double hydroxide layer is 4.7nm, the particle size of the Co-MOF nanocube is 119nm, the Co content is 3.4%, and the Ni content is 0.19%, but some cubes have collapsed; from f, it can be seen that the composite material obtained in Comparative Example 1 does not have a cubic structure, but a collapsed structure. In fact, what is obtained is a CoNi layered double hydroxide with a Co content of 2.8% and a Ni content of 0.31%. It can be seen that the excess Ni(NO3)2·6H2O over-etches the Co-MOF and cannot retain the cubic structure inside.
[0069] Application Example 1
[0070] Using H2O2 as a coreactant, without using a coreaction promoter (blank control group) or using the Co-MOF prepared according to step (1) of Example 1 and the composite materials obtained in Examples 1-4 and Comparative Examples 1-2 as coreaction promoters, and luminol as a chemiluminescent molecule, a chemiluminescent system was constructed to detect the luminescence intensity when the above coreaction promoters were used. The specific steps are as follows:
[0071] 0.0048g of luminol was added to 250mL of Na2CO3-NaHCO3 buffer solution and uniformly dispersed (pH=9). 3mL of the buffer solution with luminol added was taken, and 30μL of H2O2 (10mM) and co-reaction promoter dispersion (10mg / mL, with Na2CO3-NaHCO3 buffer solution as solvent) were added respectively, and the luminol chemiluminescence signal was measured with a chemiluminometer. The results are shown in Figure 2 As shown, 10:1, 6:1, 4:1:, 2:1 and 1:1 correspond to Examples 1-4 and Comparative Example 1, respectively.
[0072] Depend on Figure 2 It can be seen that when the composite material obtained in Example 1 is used as a coreaction promoter, the strongest chemiluminescent signal is obtained. The chemiluminescence intensities of the blank control group and the composite materials obtained in Co-MOF, Comparative Example 1, and Examples 1-4 as coreaction promoters are 10, 2532, 4072, 5877, 7309, 8830, and 6518, respectively. It can be seen that relative to the blank control group, the addition of Co-MOF as a coreaction accelerator, and the composite material obtained in Comparative Example 1 as a coreaction promoter, the luminescence intensity of the composite materials obtained in Examples 1-4 as coreaction promoters is 587.7-883.0 times, 2.3-3.5 times, and 1.4-2.2 times that of the blank control group, Co-MOF, and the composite material obtained in Comparative Example 1, respectively.
[0073] Application Example 2
[0074] Using uric acid as the substance to be detected, a chemiluminescence detection system was constructed to detect the concentration of uric acid.
[0075] 0.0048 g of luminol was added to 250 mL of Na2CO3-NaHCO3 buffer solution (pH = 9). 3 mL of the buffer solution was taken, and 30 μL of H2O2 (10 mM), the composite material obtained in Example 2 (10 mg / mL), and uric acid were added respectively, and the luminol chemiluminescence signal was measured using a chemiluminometer.
[0076] Different concentrations of uric acid aqueous solution (10 -4 -10 -8M) on the luminol chemiluminescence intensity in the system to draw a bar graph and a linear relationship graph, the results are as follows Figure 3 and Figure 4 As shown. Since uric acid can quench the active oxygen produced by hydrogen peroxide and reduce the chemiluminescent signal of luminol. Therefore, as the concentration of uric acid increases, the chemiluminescent signal in the system gradually decreases, and the degree of reduction shows a good linear relationship (R 2 =0.99), to detect the uric acid concentration.
[0077] In addition, in order to prove that the constructed uric acid detection system has good reproducibility, the application example was repeated 5 times, and the chemiluminescence intensity was Figure 5 As shown in the figure, the measured luminol luminescence intensity does not differ much, indicating that the chemiluminescence detection system composed of the composite material prepared by the present invention has very good stability in detecting uric acid. The above experiment was carried out using the composite materials obtained in Examples 1 and 3-4, and similar results were obtained.
[0078] Anti-interference ability test:
[0079] 0.0048 g of luminol was added to 250 mL of Na2CO3-NaHCO3 buffer solution (pH = 9). 3 mL of the buffer solution was added with H2O2 (10 mM), the composite material obtained in Example 2 (10 mg / mL), uric acid (10 -4 M) and 30 μL of aqueous solutions of metal salts of different valence states, and the luminol chemiluminescence signal was measured using a chemiluminescence instrument.
[0080] The aqueous solutions of metal salts with different valence states are KCl, MgCl2, CaCl2, AlCl3, NaCl, ZrCl4, and ZnCl2, respectively, and the concentration of each metal ion is 10 -4 M. Test results are as follows Figure 6 As shown, the interfering ion K was added + Mg 2+ , Ca 2+ 、Al 3+ 、Na + 、Zr 4 + and Zn 2+ The chemiluminescence intensity after addition is not much different from that without adding metal ions (UA) (the specific luminescence intensity is: K + :4332、Mg 2+ :4800, Ca 2+ :4620、Al 3+ :4700、Na + :4235、Zr 4+ :4605、Zn2+ :4732, UA:4500), indicating that metal ions have no significant effect on the quenching of luminol chemiluminescence by uric acid in the system. - Therefore, it also indirectly shows that Cl - There is no obvious effect on the quenching of luminol chemiluminescence by uric acid in the system, which proves that the chemiluminescence detection system constructed using the composite material prepared by the present invention has a strong anti-interference ability. The chemiluminescence detection system constructed using the composite material prepared by the present invention not only has strong anti-interference for KCl, CaCl2 and NaCl commonly present in uric acid, but can accurately test the concentration of uric acid; at the same time, it also has strong anti-interference for MgCl2, AlCl3, ZrCl4, and ZnCl2, indicating that the composite material has strong anti-interference for metal ions of each valence state, has a broad spectrum, and can be used for the detection of other substances. The above experiment was carried out using the composite materials obtained in Examples 1 and 3-4, and similar results were obtained.
[0081] The above results show that the composite material of CoNi layered double hydroxide and metal organic framework compound prepared by the present invention has super high activity when used as a co-reaction accelerator of luminol-hydrogen peroxide, and can greatly improve the chemiluminescence of the luminol-hydrogen peroxide system. The uric acid detection system constructed based on this material has high sensitivity, wide detection concentration range, strong anti-interference ability and good reproducibility, providing a new method for chemiluminescence analysis detection.
[0082] While preferred embodiments of the present invention have been shown and described, it is contemplated that those skilled in the art may devise various modifications of the present invention within the spirit and scope of the appended claims.
Claims
1. A composite material of CoNi layered double hydroxide and a metal organic framework compound, comprising: CoNi layered double hydroxide outer layer and Co-organic framework compound (Co-MOF) nanocubes wrapped inside it.
2. The composite material according to claim 1, characterized in that The average particle size of the composite material is 150-200 nm, the average thickness of the double hydroxide sheet structure in the outer layer of the CoNi layered double hydroxide is 1-5 nm, and the average particle size of the Co-MOF nanocube is 95-148 nm.
3. The composite material according to claim 1 or 2, characterized in that: The content of Co in the composite material is 3.0%-5.5%, and the content of Ni is 0.02%-0.20%.
4. A method for preparing the composite material according to any one of claims 1 to 3, comprising the following steps: The Co-MOF nanocube raw material, Ni source and solvent are mixed and then subjected to etching reaction to obtain the composite material.
5. The preparation method according to claim 4, characterized in that: The Ni source is Ni(NO3)2·6H2O, and the mass ratio of the Co-MOF nanocube raw material to the Ni source is 10-1.5:
1.
6. The preparation method according to claim 4, characterized in that: The average particle size of the Co-MOF nanocube raw material is 100-150 nm.
7. The method according to claim 4, characterized in that The solvent is ethanol, and the usage ratio of the Co-MOF nanocube raw material to the solvent is 1 mg: 0.7-1.2 mL.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The etching reaction is carried out under ultrasonic conditions, the frequency of the ultrasound is 35-45 Hz, and the time is 50-70 min.
9. Use of the composite material according to any one of claims 1 to 3 or the composite material obtained by the preparation method according to any one of claims 4 to 8 in chemiluminescence detection.
10. The use according to claim 8, characterized in that: The chemiluminescence detection is uric acid detection.